Tourism - Neil McBurbey (Prentice-Hall, 1996)
The book features up-to-date authentic professional texts, wide-ranging coverage of the field of international tourism, contextualised exercises offering a wide range of techniques for developing effective reading skills, glossary of professional vocabulary.